The efficient synthesis of 2-arylamino-2-imidazolines, 2-heteroaryl- substituted benzimidazoles, and their morpholin-4-ylmethyl derivatives - Servi, Süleyman (My University, 2002)
2-Heteroaryl-substituted 1H-benzimidazoles were synthesized in good yields by heating the HSO3 adducts of heteroaromatic aldehydes with o-phenylenediamine in DMF under reflux. This procedure is more general and shorter than earlier methods. 2-Arylamino-2-imidazolines were prepared by heating dimethyl aryldithioimidocarbonates and ethylenediamine under reflux. The imine-enamine tautomerization of 2-arylamino-2-imidazolines was investigated by means of 1H-NMR spectroscopy. Morpholin-4-ylmethyl derivatives of the benzimidazole and imidazoline products were synthesized regioselectively by treatment with morpholine and formaldehyde.
Keywords: 2-arylamino-2-imidazolines; 2-Substituted benzimidazoles; Dimethyl aryldithioimido-carbonates; Imine-enamine tautomerization